PENINGKATAN PEMAHAMAN SISWA TERHADAP KONSEP PERAMBATAN BUNYI MELALUI MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DI KELAS V UPT SPF SD INPRES SERO - Fitri Randani Irwan; Syarifah Aeni Rahman; Emil (STKIP Subang, 2024)
FITRI RANDANI IRWAN, 2024. Improving Students' Understanding of Sound Propagation Concepts through Cooperative Learning Model Student Team Achievement Division (STAD) in Class V UPT SPF SD Inpres Sero, Classroom Action Research. This research employs classroom action research, with the researcher acting as the teacher and assisted by two observers who collect and analyze data. The study is based on the reality that many elementary school students still struggle to understand the concept of sound propagation and are less engaged in group learning. One issue faced by elementary students is the material on sound propagation through liquids and solids. To address this, the cooperative learning model STAD was implemented. This research is formulated as follows: can students' understanding of sound propagation concepts be improved through the cooperative learning model Student Team Achievement Division (STAD) in Class V UPT SPF SD Inpres Sero? Based on the research findings, it was obtained that through the STAD cooperative learning model, students’ understanding of sound propagation concepts increased at UPT SPF SD Inpres Sero. The STAD cooperative learning was conducted through seven stages: preparation for learning, presentation of material, group learning, checking group learning outcomes, individual testing, test checking, and group rewards. The data is presented in verbal form to determine the improvement in students' understanding of sound propagation concepts using the STAD model. This data relates to student/teacher activity, student engagement in the learning process, students' enthusiasm during group and class discussions, students' understanding in answering tests both orally and in writing, students' responses to learning, and achievement of learning outcomes.